Empowering Employees Through Training and Development: A Study on Performance Enhancement at Paper Manufacturing Company - ‘Aeisyah Bt Ahmad Khairul; Siby James; Nur Izzati Bt Noor Zaimi; Nur Fatin Alimah Zolkepli; Nur Fatin Jufri; Nur Hanis Zulaiqah Muhammad Shariff; Prem Gupta; Kee Daisy Mui Hung (Asia Pacific Journal of Management and Education (APJME), 2024)
The paper industry faces constant challenges, requiring a workforce with strong adaptability and technical skills. Nippon Paper Industries Co., Ltd., a frontrunner in paper products, explores how training empowers employees and boosts performance. The objective of this research is to evaluate the effectiveness of training and development programs in enhancing employee performance in Nippon Paper Industries. The study gathered quantitative data through online surveys that were administered to 150 employees selected via stratified random sampling. The findings indicate a strong positive correlation between training and development programs and employee performance. The majority of respondents reported the effectiveness of training programs in enhancing skills, boosting productivity, and reducing turnover. However, the alignment of training needs with organizational strategy was perceived as less effective, with a significant portion of respondents expressing neutral opinions. By implementing structured training programs and evaluating their effectiveness, organizations can enhance employee satisfaction, productivity, and retention.